2017
DOI: 10.20474/jahss-3.5.2
|View full text |Cite
|
Sign up to set email alerts
|

A review of TRIZ and its benefits & challenges in stimulating creativity in problem solving of pre-university students: A TARUC case study

Abstract: Abstract.Creativity is the ability of solving problem. Problem solving is an important skill students must learn in order to cope with the demand of the 21 st century which saw unprecedented growth in technology. Theory of Inventive Problem Solving (TRIZ), which emerged from Russia in the 1960s, has been introduced to Tunku Abdul Rahman University College (TARUC) since 2011 to train undergraduate and pre-university students in problem solving. There are many TRIZ literatures on how TRIZ provides support to und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(23 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…Moreover, they found that TRIZ increased the creativity with which students designed products, including the capability to develop and implement ideas. Also, as revealed in [26], the TRIZ program improved students' efficacy in problem finding, idea finding, and overall problem-solving, in addition to improving students' creativity.…”
Section: Discussionmentioning
confidence: 87%
“…Moreover, they found that TRIZ increased the creativity with which students designed products, including the capability to develop and implement ideas. Also, as revealed in [26], the TRIZ program improved students' efficacy in problem finding, idea finding, and overall problem-solving, in addition to improving students' creativity.…”
Section: Discussionmentioning
confidence: 87%
“…Sheng and Howa highlighted that TRIZ tools could help users identify the problem better (Sheng and Howa, 2016). It is illustrated that TRIZ could enhance users' problem finding and understanding abilities (Keong et al, 2017;Harlim and Belski, 2015). TRIZ also exploits valuable tools, such as functional analysis or su-field analysis, to break the problem structure based on its elements, analyze them and find the point where the real problem lies (Tomlinson et al, 2002;Rantanen et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The previous researchers have analyzed the impact of particular memory behaviour on the student's performance, but they have not conducted a comparative study to identify the most appropriate memory strategy among a range of memory strategies that can be used by the students (Bergin & Bergin, 2014;Gutchess & Indeck, 2009;Hendelman, Humphreys, & Skinner, 2017;Keong, Yip, Swee, Toh, & Tai, 2017;Malroutu, 2017). Moreover, much of the previous researchers have utilized a theoretical approach to determine the importance of memory strategies.…”
Section: Literature Gapmentioning
confidence: 99%